2015
DOI: 10.1039/c4ra15974h
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of cerium doped siloxane–PMMA hybrid coatings with high anticorrosive performance

Abstract: Novel environmentally compliant Ce(IV) doped siloxane-PMMA coatings exhibiting dense cross-linked structure, high thermal stability, unique anticorrosive performance and self-healing ability.This study reports on the characterization of cerium doped organic-inorganic hybrid coatings by correlating their structural properties with the corrosion protection efficiency of coated carbon steel.The films were prepared via the sol-gel route from radical polymerization of methyl methacrylate (MMA) with 3-methacryloxy p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 25 publications
(51 reference statements)
3
50
1
Order By: Relevance
“…The excellent performance of the primer free coating was explained by the high connectivity of reticulated sub-nanometric silica domains densely interconnected by short PMMA chain segments. Another results that confirmed the viability of thin hybrid films as efficient corrosion barrier have been reported in the study of Harb et al [11]. The authors showed that the addition of cerium (IV) salt into PMMA-silica system results in a further improvement of the corrosion resistance and durability of the coatings applied to polished carbon steel by dip-coating.…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations
“…The excellent performance of the primer free coating was explained by the high connectivity of reticulated sub-nanometric silica domains densely interconnected by short PMMA chain segments. Another results that confirmed the viability of thin hybrid films as efficient corrosion barrier have been reported in the study of Harb et al [11]. The authors showed that the addition of cerium (IV) salt into PMMA-silica system results in a further improvement of the corrosion resistance and durability of the coatings applied to polished carbon steel by dip-coating.…”
Section: Introductionsupporting
confidence: 57%
“…Detailed investigation of the structural effects of cerium species has shown that reduction of Ce(IV) ions not only catalyzes a higher connectivity of the silica phase, but also enhances the polymerization of organic moieties. The resulting enhancement of the overall network connectivity leads to an improvement of the thermal stability of the hybrids, as evidenced by the results of the thermogravimetric analysis [11].…”
Section: Pmma-silica Hybrid Modified With Ce(iv) Salt For Self-healinmentioning
confidence: 89%
See 2 more Smart Citations
“…Recently, Harb et al have reported a similar study where they also correlated the structural properties of cerium doped organic-inorganic hybrid coatings with their efficiency for the corrosion protection of carbon steel. The films were prepared via the sol-gel route from radical polymerisation of methyl methacrylate with 3-methacryloxy propyltrimethoxysilane followed by acidic hydrolysis and condensation of tetraethoxysilane [37]. A promising research line consists in introducing phosphorus precursors into organic-inorganic hybrid sol-gel coatings.…”
Section: Introductionmentioning
confidence: 99%